Cholinesterase inhibitors in Alzheimer's disease and Lewy body spectrum disorders: the emerging pharmacogenetic story - Lam, Benjamin (BioMed Central, 2009)
This review provides an update on the current state of pharmacogenetic research in the treatment of Alzheimer's disease (AD) and Lewy body disease (LBD) as it pertains to the use of cholinesterase inhibitors (ChEI). AD and LBD are first reviewed from clinical and pathophysiological perspectives. This is followed by a discussion of ChEIs used in the symptomatic treatment of these conditions, focusing on their unique and overlapping pharmacokinetic and pharmacodynamic profiles, which can be used to identify candidate genes for pharmacogenetics studies. The literature published to date is then reviewed and limitations are discussed. This is followed by a discussion of potential endophenotypes which may help to refine future pharmacogenetic studies of response and adverse effects to ChEIs.